MoS2-Based nanocomposite for synergistic chemo-photothermal cancer therapy - Maryam Mahmoodabadi; Mohammad Taghi Goodarzi; Nasrin Salehi; Alireza Jalali; Ehsan Zahedi (Scientific Reports)
Abstract MoS₂ nanoflakes are emerging as a promising material for photothermal therapy due to their high absorption in the NIR region, large specific surface area, biocompatibility, efficient photothermal conversion, and ability to be functionalized for targeted therapy. In this paper, MoS₂ nanoflakes were incorporated to Fe3O4 nanoparticles, gold nanorod (GNR), and copper sulfide (CuS) (MCG nanocomposite) to investigate chemo-photothermal therapy in this nanocomposite. The structural and optical properties of the MCG nanocomposite were characterized by X-ray diffraction (XRD), Transmission electron microscopy (TEM), Zeta potential, Dynamic Light Scattering (DLS), Fourier transform infrared (FTIR), and Ultraviolet-visible (UV-Vis) spectroscopies. The photothermal results of samples indicated that MCG nanocomposite produced higher photothermal heat than each individual sample alone (808 nm NIR laser irradiation at a power density of 1 W/cm2 after 10 min). Under NIR laser irradiation, the release of DOX was greatly accelerated at pH = 5.5 as compared to pH = 7.4. So, this nanocomposite can be used as dual responsive systems, with DOX release controllable through pH and NIR irradiation. Finally, MTT assays experiment showed that, using NIR irradiation, the relative viabilities of HeLa cells decreased when the concentration of drug increased. Hence MCG nanocomposite could be a potent system for targeted drug delivery and synergistic chemo-photothermal cancer therapy.